2020
DOI: 10.3390/s20010315
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Piezoelectric AlN Thin Film with SU-8/PDMS Supporting Layer for Flexible Sensor Array

Abstract: This research focuses on the development of a flexible tactile sensor array consisting of aluminum nitride (AlN) based on micro-electro-mechanical system (MEMS) technology. A total of 2304 tactile sensors were integrated into a small area of 2.5 × 2.5 cm2. Five hundred nm thick AlN film with strong c-axis texture was sputtered on Cr/Au/Cr (50/50/5 nm) layers as the sacrificial layer coated on a Si wafer. To achieve device flexibility, polydimethylsiloxane (PDMS) polymer and SU-8 photoresist layer were used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The complete removal of unexposed SU-8 during the earlier development step is a critical requirement at this stage to avoid the residual SU-8 ( Figure 4 a) to interfere with MPTMS binding on gold. Incomplete removal would result in patchy transfer of gold electrode lines to PDMS and thereby breaking continuity of electrode lines [ 13 ]. Moreover, we noticed that upon sacrificial release, this thin residual SU-8 layer transfers to PDMS and greatly reduces the thermal bonding capability of PDMS to CMOS chip.…”
Section: Resultsmentioning
confidence: 99%
“…The complete removal of unexposed SU-8 during the earlier development step is a critical requirement at this stage to avoid the residual SU-8 ( Figure 4 a) to interfere with MPTMS binding on gold. Incomplete removal would result in patchy transfer of gold electrode lines to PDMS and thereby breaking continuity of electrode lines [ 13 ]. Moreover, we noticed that upon sacrificial release, this thin residual SU-8 layer transfers to PDMS and greatly reduces the thermal bonding capability of PDMS to CMOS chip.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that the maximum power and the corresponding peak voltage generated by the sensor were 5.6 µW and 690 mV, respectively. Yeo et al [8] developed a flexible tactile sensor array consisting of aluminum nitride (AlN) thin film as PZT material deposited in Si wafer for energy generation when the sensor is subject to mechanical stimulus.…”
Section: Related Workmentioning
confidence: 99%
“…Zhang, et al reported that the coating of photoresist SU-8 on a silicon-(100) wafer substantially improves the flexibility and can be used for high-performance flexible electronics [93], whereas developed glass/SU8-gold electrodes by Matarèse, et al were extremely transparent, and stable in the biological culture medium, which exhibited biocompatibility similar to glass [94]. Flexible and bendable (to 90 • ) tactile sensor arrays were also developed by Yeo, et al, consisting of aluminum nitride, based on micro-electro-mechanical system (MEMS) technology, where polydimethylsiloxane (PDMS) and a SU-8 photoresist layer were used as the supporting layers [95].…”
Section: High-k Dielectric Polymersmentioning
confidence: 99%